IMPLEMENTASI KARAKTERISTIK GAYA BELAJAR (4 MAT SYSTEM) PESERTA DIDIK PRODI PENDIDIKAN AGAMA KRISTEN DI STT KRISTUS ALFA OMEGA, SEMARANG TAHUN AJARAN 2017/2018 - Rombe, Eni (Sekolah Tinggi Teologi Kristus Alfa Omega, 2018)
Learning style learning style is the best way used by students in learning to receive, absorb and process information received. This study aims to describe the characteristics of student learning styles which consist of the characteristics of the learning style of 4MAT System. The 4MAT System learning style developed by Bernice McCarthy proclaims four learning models namely; analytic learning, imaginative learning, common sense learning and dynamic learning. This study uses quantitative research methods with a type of descriptive research. With the research subject were students of the Christian Education Study Program at STT Kristus Alfa Omega, Semarang, which numbered 41 people. The technique of collecting data is done through questionnaires or questionnaires. The results showed the level of implementation of the 4MAT System learning style by the Christian Religious Education Study Program at the STT Kristus Alfa Omega, Semarang in the 2017/2018 academic year with a value of 77,177% which was at a high percentage, between (61-80).